Autism, menstruation and mental health- a scoping review and a call to action - Joanna Skommer; Joanna Skommer; Krish Gunesh (Frontiers in Global Women's Health)
IntroductionThere is increasing evidence regarding the mental health implications of cyclical hormonal fluctuations associated with menstruation, as well as of key reproductive transitions (menarche and menopause), in typically developing individuals. Autism spectrum disorder (ASD), a complex neurodevelopmental condition, may predispose individuals to maladaptive responses to life changes such as menstruation. Despite the importance of this topic, research relating to menstrual experiences across the lifespan of autistic adults remains scarce, largely due to the intersecting effects of multiple marginalizing characteristics experienced by this population. This research gap significantly limits our understanding of how menstruation impacts the mental health of autistic individuals.ObjectivesThe purpose of this scoping review was to examine existing evidence about menstrual experiences, including menarche and menopause, and their impact on mental health among autistic individuals, and propose a biopsychosocial framework for the complex interplay of individual, healthcare, and societal vulnerabilities that predispose autistic individuals to negative menstrual experiences.MethodsA scoping review of original articles, quantitative and qualitative, published in English from 1980 onwards, identified through search of online databases and reference lists, using PRISMA extension for scoping reviews.ResultsA total of 45 studies were identified to meet the specified inclusion and exclusion criteria. The key emerging themes were the mental health impact of menstruation, the occurrence and experience of menstrual disorders among autistic individuals, as well as support strategies and healthcare utilization by that population.ConclusionsAlthough our current knowledge on menstrual health specific to autistic individuals is still scant, it nevertheless raises significant concerns regarding potential challenges. The findings of this study have been placed within the bio-psycho-socio-cultural framework to emphasize that menstrual experiences occur within the context of person-environment transactions, and that autistic individuals are vulnerable to negative menstrual experiences because of adverse or non-facilitative societal and healthcare environments. Further large-scale studies addressing identified gaps (e.g., influence of gender diversity, impact of medical comorbidities, trauma and stigma) is warranted.Systematic Review Registrationhttps://osf.io/gxurq.